The EMESRT Approach to Equipment Design - Bringing End Users into the Picture (The Australasian Institute of Mining and Metallurgy, 2010)
The Earth Moving Equipment Safety Round Table (EMESRT) was established by mining companies in 2006 to influence manufacturer's equipment design through a process of engagement. 2010 EMESRT member companies include Anglo American, Barrick, BHP Billiton, Centennial Coal, Collahausi, Newcrest, Newmont, Rio Tinto, Vale and Xstrata.Driven by a persistent need for retrofits to new equipment, such as haul trucks, EMESRT initially engaged with Surface Equipment Manufacturers including Caterpillar, Komatsu, Leibherr, Hitachi, Le Tourneau and Terex. These OEMs responded positively to the EMESRT initiative, welcoming the opportunity for dialogue with an aligned industry regarding human factors issues related to equipment design, rather than needing to respond to the disparate range of demands for design modifications previously received from individual customers. This engagement process is about making global sustained changes within the OEM organisations and within the mining companies. It is a very international exercise. For example, over two weeks in September 2010, a total of 21 different miners from ten different companies travelled from Australia, South Africa, Canada, Brazil, Singapore and the United States to engage with OEM counterparts who assembled from the United States, Japan, France, Sweden, Finland and Germany. EMESRT Surface Group representatives completed a whirlwind tour of the major North American manufacturers of mining equipment. Starting in Dallas (Atlas Copco, LeTourneau), this tour passed through Gainesville (Sandvik), Newport News (Liebherr), Guelph - Ontario (Hitachi) and Milwaukee (P&H Mining/Joy Global; Bucyrus), before winding up in Peoria, Illinois (Komatsu, Caterpillar). Over nine meetings, this group engaged with 129 individuals from nine OEMs. The EMESRT group welcomed miners from four non-member companies to come along for the meetings. These companies are Syncrude Canada Ltd, the Kearl Oil Sands Project - Imperial Oil (ESSO), Suncor Energy Ltd and Teck Resources Ltd.Other mining industry sectors have now expanded the EMESRT scope from surface mining to include exploration and underground mining equipment. In 2009, EMESRT was organised into four Technical Groups, consisting of EMESRT member company representatives, to focus on engagement with OEMs of surface, underground coal and soft rock, underground hard rock, and exploration drilling equipment. An advisory group has been formed to coordinate activities between all workgroups and provide strategic direction and cohesion between all activities. The Minerals Industry Safety and Health Centre (UQ-SMI) facilitates and coordinates all EMESRT activities on behalf of member companies. Building on successes with individual Surface Mining OEMs, EMESRT now aims to help OEMs in their transition to a sustainable design process that will incorporate and address specific design philosophies at the concept phase of design, so that significant improvements can be made up front for little cost within the overall budget. EMESRT members plan to educate all stakeholders, internally, within their own companies, and externally, by addressing industry associations, regulators and other end users about new ways of evaluating equipment design based on EMESRT purchasing specifications. This presentation will outline the EMESRT approach and report on progress in 2010.